The impossible trinity (aka the policy Trilemma): The encyclopedia of financial globalization - Joshua Aizenman (University of California, Economics Department, 2010)
The policy Trilemma (the ability to accomplish only two out of three policy objectives -financial integration, exchange rate stability and monetary autonomy) continues to be a valid macroeconomic framework. The financial globalization during 1990s-2000s reduced the weighted average of exchange rate stability and monetary autonomy. An unintended consequence of financial globalization has been the growing exposure of developing countries to costly capital flights and deleveraging crises. Emerging Markets responded by adding financialstability to the three Trilemma policy goals, coupling their growing financial integration with large hoarding of international reserves, as means of self-insuring their growing exposure to financial-turbulences.
Keywords: 330; Mundell-Fleming-Modell; Wechselkurssystem; Wechselkurspolitik; Geldpolitik; Kapitalmobilität; Globalisierung; Internationaler Finanzmarkt; Theorie; Welt